(untitled) (Innovative professional education, 2024)
The article highlights the peculiarities of youth entrepreneurship in Ukraine and state support for students under martial law. Youth entrepreneurship is seen as a key factor in the economic recovery of post-war Ukraine. Various initiatives aimed at supporting youth entrepreneurship are discussed, involving both government agencies and non-governmental organisations. In addition, the potential for young entrepreneurs to continuously update their skills and knowledge to meet modern standards is highlighted.